Nutritional Content and Acceptability of Vegetable Sausage as an Alternative Source of Protein and Fiber - Kunaepah, Uun; Sulistiyono, Priyo; Estuti, Wiwit (Jurnal Medisci, 2024)
Nutrition problems in Indonesia are still relatively high. SSGI results (2021) show that malnutrition is 17.1% and stunting is 24.4%. Lack of food consumption, especially protein, is one of the causes. Utilization of tofu dregs is still very low, as is banana blossom. Tofu dregs and banana blossoms have quite a high protein and fiber content. Tofu dregs and banana blossoms have the potential to become a high-nutrient food product that is suitable for consumption and has economic value. This research is a follow-up research from organoleptic tests, finding that vegetable sausages have organoleptic qualities that are no less than commercial sausages. This research aims to conduct laboratory tests for protein and fiber content and tests for the acceptability of vegetable sausages. This type of research is experimental, by design of two groups with control. Test acceptability with the method Visual Comstock by looking at leftovers. The acceptability test was conducted on 51 children in grades IV and V at SDN Pamitran-Cirebon who met the screening criteria. The treatment group consisted of 24 children, and the control group consisted of 27 children. Sample assignment was carried out randomly. Analysis of crude protein content using the IK-03/LAKP/SOP.10 method. Analysis of oil fiber content IK-13/LAKP/SOP.10. Analysis of the difference in receptivity test using the t-test of unpaired data. The research results showed that the protein content of vegetable sausages was (7.54%), slightly lower than commercial sausages (9.29%). The crude fiber content of vegetable sausages (3.48%) is higher than commercial sausages (2.10%). Vegetable sausages have the same acceptability as commercial sausages, with a good acceptability value of 100%. It has been proven that vegetable sausages can be used as an alternative food source of high protein and fiber at a relatively cheaper price.